Advancing Climate Security in the Mediterranean: Toward a Shared Agenda for Action - Pacillo, Grazia; Mastrorillo, Marina; Taiwo, Ibukun (CGIAR, 2023)
On June 26, 2023, CGIAR Focus Climate Security, supported by the CGIAR Initiatives on Climate Resilience; Fragility, Conflict, and Migration; and the Alliance of Bioversity International and CIAT; under the patronage of the Italian Ministry of Foreign Affairs and International Cooperation, convened a high-level event to discuss a common vision of the climate, migration, and security nexus in the Mediterranean region.